The Role of Optineurin in Antiviral Type I Interferon Production - Outlioua, Ahmed; Pourcelot, Marie; Arnoult, Damien (Frontiers in Immunology, 2018)
After a viral infection and the stimulation of some pattern-recognition receptors (PRRs) as the TLR3 in the endosomes or the RIG-I-like Receptors (RLRs) in the cytosol, activation of the IKK- related kinase TBK1 leads to the production of type I Interferons (IFNs) after phosphorylation of the transcription factors IRF3 and IRF7. Recent findings indicate an involvement of K63-linked polyubiquitination and of the Golgi-localized protein Optineurin (OPTN) in the activation of this crucial kinase involved in innate anti-viral immunity. This review summarizes the sensing of viruses and the signaling leading to type I IFN production following TBK1 activation through its ubiquitination and the sensing of ubiquitin chains by OPTN at the Golgi apparatus.